Personalized System of Instruction Models Using â€œPOJOKâ€ Digital Module Based Toward Basket Ball Learning Outcome - Juditya, Silvy; Zakaria, Dhani Agusni; Hardi, Veny Juaniarni; Rusmana, Ruslan (Universitas Suryakancana, 2021)
The development of technology demands a lot of changes in the world of education, as well as in physical education learning so that physical education teachers in schools must be able to choose and apply learning models that can be juxtaposed with technology-based learning media, therefore the purpose of this study is to determine the effect of learning models. personalized system of instruction (PSI) based on the application of the electoral module